The Association Between Parenting, Social Interaction, Social Values, and Adolescent Mental Health: A Cross-Sectional Study in Palu, Indonesia - Mangundap, Selvi A; Munir, Muh Ardi; Rahman, Nurdin; Supirno, Supirno; Amyadin, Amyadin (Journal of Health and Nutrition Research, 2025)
Adolescent mental health is a critical determinant of developmental outcomes, influenced by factors such as parenting, social interaction, and social values. However, empirical research examining these variables concurrently is limited, particularly in urban Indonesian schools. This study aimed to analyze the relationship between parenting styles, social interaction, and social values with the mental health of students at SMPN 9 Palu. A quantitative, cross-sectional design was employed in February 2025, involving 93 eighth-grade students selected through purposive sampling. Data were collected using validated questionnaires for parenting, social interaction, and social values, while mental health was assessed using the Strengths and Difficulties Questionnaire (SDQ). The relationships between variables were analyzed using the Chi-Square test. The analysis revealed that parenting (p=0.001), social interaction (p=0.033), and social values (p=0.034) were all significantly associated with adolescent mental health. These findings underscore the necessity of integrated, multi-level interventions targeting family and school environments to foster adolescent psychological well-being. The study concludes that poor parenting, inadequate social interaction, and low social values are significant risk factors for mental health disorders among this population, confirming the pivotal role of the socio-familial environment